mRNA in situ hybridization analysis of MMP-9 in chronic lymphocytic leukemia - Jaafar, Abdulkareem M.; Majeed, Ban Abbas A.; Al-Rubaie, Haythem A.M. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Several factors render chronic lymphocytic leukemia (CLL) an interesting subject for study by researchers. These include marked progress in understanding the molecular biology of normal and neoplastic lymphocytes and recent advances in molecular genetics techniques. Among molecular markers, matrix metalloproteinase-9 (MMP-9), have been widely studied.Objectives: The aim of the study is to evaluate the role of MMP-9 in the pathogenesis of CLL and to assess its prognostic role.Patients and methods: A retrospective cross-sectional study done on 60 patients with chronic lymphocytic leukemia compared with 20 controls (anemic patients), all recruited at the Medical City Teaching Hospital laboratories from January 2004 to December 2007. The bone marrow biopsy of each patient was re-examined histologically. MRNA-In situ hybridization was performed to detect MMP-9.Results: The frequency of MMP-9 positivity was 78.3% (47 of 60 cases). A significant inverse correlation was found between increasing MMP-9 scores and lower PCV level. A significantly larger number of patients with high score were associated with advanced modified Rai stage than patients with low score. In addition, there was a significant positive correlation between increasing scores of MMP-9 and advancing clinical stage.Conclusion: MMP-9 positivity was high and the score was significantly associated with advanced clinical stage of the disease